Correlation between Interleukin-4 and Interleukin-6 and auto antibodies in Systemic Lupus Erythematosus. - Abdualkader, Sajid N.; Wahab Al-Shaikly, Abdul-; Al-Mousawy, Khalida M.; Al-Ezzi, Mustafa; Hasso, Maan G.; Hassan, Zena E. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: There is a general acceptance which illustrated that auto antibodies act as a central immunological disturbance in most of the auto immune diseases, among these auto immune diseaselies the SLEPatients and Methods: Thirty five patients with SLE were compared to twenty age and sex matched, control subjects and studied for the presence of auto antibodies, plus IL-4 and IL-6 using Elisa method and immune fluorescent method (for ANA only)Results: Data showed that IL-6 detectable levels were statistically significant in patients with positive anti ds-DNA, but not significant statistically in ANA positive patients although it was detected in 24 (70.6%) of positive ANA patients, while there was no statistically significant correlation between IL- 4 detectable level and autoantibodies production.Conclusion: There is apparently a positive correlation between IL-6 and anti ds DNA production in lupus patients.